Fully Integrated, Stretchable, Wireless Skin‐Conformal Bioelectronics for Continuous Stress Monitoring in Daily Life. Issue 15 (15th June 2020) - Kim, Hojoong; Kim, Yun‐Soung; Mahmood, Musa; Kwon, Shinjae; Zavanelli, Nathan; Kim, Hee Seok; Rim, You Seung; Epps, Fayron; Yeo, Woon‐Hong
Abstract: Stress is one of the main causes that increase the risk of serious health problems. Recent wearable devices have been used to monitor stress levels via electrodermal activities on the skin. Although many biosensors provide adequate sensing performance, they still rely on uncomfortable, partially flexible systems with rigid electronics. These devices are mounted on either fingers or palms, which hinders a continuous signal monitoring. A fully‐integrated, stretchable, wireless skin‐conformal bioelectronic (referred to as "SKINTRONICS") is introduced here that integrates soft, multi‐layered, nanomembrane sensors and electronics for continuous and portable stress monitoring in daily life. The all‐in‐one SKINTRONICS is ultrathin, highly soft, and lightweight, which overall offers an ergonomic and conformal lamination on the skin. Stretchable nanomembrane electrodes and a digital temperature sensor enable highly sensitive monitoring of galvanic skin response (GSR) and temperature. A set of comprehensive signal processing, computational modeling, and experimental study provides key aspects of device design, fabrication, and optimal placing location. Simultaneous comparison with two commercial stress monitors captures the enhanced performance of SKINTRONICS in long‐term wearability, minimal noise, and skin compatibility. In vivo demonstration of continuous stress monitoring in daily life reveals the unique capability of the soft device as a real‐world applicable stress monitor. Abstract : Continuous, wireless monitoring of stress in daily life is enabled by the development of a fully integrated, stretchable, skin‐conformal bioelectronic that includes nanomembrane sensors and stretchable circuits for a highly sensitive galvanic skin response and temperature monitoring with negligible motion artifacts.